Posthuman Dataflows: Passive Data Migration and Algorithmic Sovereignty in East Africa - Ndemo, Elijah B.; Mkalama, Ben (Journal of Posthumanism, 2025)
This study conceptualizes Passive Data Migration (PDM) as a posthuman process through which health data, infrastructures, and algorithms acquire agency in shaping governance across East Africa. As predictive analytics, artificial intelligence, and global health platforms collect and transmit sensitive information, data move beyond national and human control, enacting new relations of power between human and nonhuman actors. Drawing on mixed-methods research in six East African nations, the study reveals how inadequate local infrastructure, donor dependency, and external demand create a digital ecology where databases, cloud systems, and algorithms function as autonomous participants in decision-making. These findings are interpreted through the lenses of data colonialism and data justice, showing how posthuman entanglements displace traditional ideas of sovereignty and accountability. The article argues for re-imagining data governance as a distributed ethical field in which both human and technological entities share responsibility. It concludes by proposing a regional framework for equitable data protection that recognizes algorithmic and infrastructural agency as integral to East Africa’s digital futures.